Descriptions of two new Species of Goniozus Förster, 1856 (Hymenoptera: Bethylidae) associated with insect induced plant galls from India - Santhosh, Shreevihar; Ranjith, Avinjikkattu Parambil (Zootaxa, 2015)
Two new species of the genus Goniozus viz., Goniozus inauditus Santhosh sp. nov. and G. kuriani Santhosh sp. nov. associated with insect induced plant galls from South India are described. The parasitic relationship of Goniozus with the nonlepidopteran hosts living in the concealed habitats and their association with insect induced plant galls and its inhabitants are reviewed.  The possible host range extension of Goniozus is commented.